Hip adductor strength tests used in the context of sports: practical considerations - Oliva-Lozano, José M.; Dominguez, Stephanie; Paul, Darren; Cost, Rick; Gómez-Carmona, CarlosD. (International Journal of Sports Medicine, 2025)
Hip and groin injuries are prevalent in team sports involving high-intensity actions and multi-directional activities. A hip adductor strength test is a widely used tool to assess hip adduction strength, which is a key risk factor for these injuries. Despite its common usage, there is a lack of standardized guidelines regarding the measurement protocol, leading to inconsistent and unreliable applications. This review aims to synthesize existing research on hip adductor strength testing, highlighting the importance of developing clear guidelines for its implementation. This review covers various aspects of the test, including pre-test warm-up protocols, body positioning, device placement, test execution, verbal commands, data collection and selection, and timing of tests. Key findings suggest that standardized warm-up routines, consistent body and device positioning, clear verbal commands, and specific criteria for invalidating test trials are critical for enhancing the reliability and accuracy of the test. Furthermore, consistent timing and the documentation of test conditions are essential for effective athlete monitoring and injury prevention. By establishing and adhering to these guidelines, sports scientists and medical personnel can make well-informed decisions about athletes’ hip adduction strength, ultimately improving injury prevention and performance outcomes in sports.
Keywords: squeeze test; elite; soccer; football; testing; technology